Challenges in Palliative Care Research on Family Caregivers: Who Volunteers for Interviews? - Breen, Lauren; Johnson, Andrew; O'Connor, Moira; Howting, D.; Aoun, Samar (MARY ANN LIEBERT, INC, 2021)
Background: Interviews are a common method of data collection in palliative care research because they facilitate the gathering of rich, experiential data that are important for theory and practice. What is less clear is the extent to which those interviewed are representative of the larger group. Objective: The aim of this study was to determine if family caregivers who volunteer to be interviewed were similar or different to those who do not. Design: This study used data from the Caregiving and Bereavement study, a prospective, longitudinal mixed-methods study of family caregivers' general health, quality of life, and grief. Setting/Subjects: The 16 caregivers who volunteered to be interviewed were compared to the 20 who did not. Measurements: Comparisons were made in terms of the caregivers' demographic characteristics as well as measures of their quality of life, general health, general grief, and caregiver prolonged grief (i.e., before death). Results: Compared to caregivers who did not volunteer for an interview, those who volunteered were significantly older and reported less caregiver prolonged grief. Logistic regression showed that for each 1-unit increase in the caregiver prolonged grief score, individuals were 13% less likely to agree to an interview. Conclusions: Research findings based upon family caregivers who volunteer for research interviews might not provide a full picture of their experiences and needs. Researchers are encouraged to consider strategies that sample broadly and promote the participation of the full range of family caregivers in research to address the neglected areas of pre- A nd postdeath bereavement care.